(untitled) (Research, Society and Development, 2021)
Cardiovascular diseases (CVD) and diabetes mellitus (DM) are chronic non-communicable diseases with high prevalence. Several factors contribute to its lack of control, especially those related to pharmacotherapy, often leading to problems related to the use of medication (DTP). Objective: To identify potential DTPs for the treatment of CVD and DM, as well as associated factors, using big data from users of the Unified Health System (SUS) in a municipality. Methods: A cross-sectional study was carried out based on big data of patients for whom at least one medication was dispensed in SUS pharmacies in the primary healthcare network in April 2019 (n = 4,800). Potential DTPs involving the treatment of CVD or DM were identified based on data on medications dispensed, demographic and clinical characteristics. To classify these potential PRMs, the Pharmacotherapy Workup method was used. Logistic regression analyzes were performed to identify factors associated with identifying at least one potential MRP. Results: The results showed that 25% of the population had at least one potential DTP, with a total of 1,914 potential PRMs being identified. In the multivariate model, age group was statistically associated with the identification of at least one potential DTP. Conclusions: This study allows tracing the frequency of important potential DTPs and associated factors, pointing out some priorities that must be addressed by the public primary health care system, supporting the planning of the implementation of drug therapy management services aimed at the studied population.